Penguatan Kultur Sekolah sebagai Strategi Holistik untuk Pembentukan Karakter dan Literasi Siswa di Era Digital - Diniatul Murtafik; Ardian Syah Bahtiar; Nur Fauziyah Indah Amaliyah; Anisa Rani, Mu'allimin (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Culture plays an important role in developing students' character and improving students' literacy, especially in the digital era that reflects the 21st century. This study aims to investigate the role of school culture in fostering student character and literary development through the study of literature. The data summary consists of several articles selected using a selection process of 20 articles selected using the Publish or Perish tool. The findings of the analysis show that a school culture based on religious values and literacy is able to create a conducive and inclusive learning environment. Programs such as congregational prayer, tadarus, library optimization and community-based activities provide significant support in improving students' discipline, responsibility and literacy skills. However, the research results are based on school leadership, community involvement and policy support. This highlights the importance of holistic education in creating a school culture that is in line with globalization and digitalization trends. The findings emphasize the importance of a holistic approach in building a school culture that is relevant to the challenges of globalization and digitalization. This research makes theoretical and practical contributions to designing educational strategies that focus on strengthening school culture.